1982
DOI: 10.1159/000249948
|View full text |Cite
|
Sign up to set email alerts
|

Neurosyphilis heute

Abstract: Since there has been an increase in the number of patients suffering from syphilis during the last 2 decades, neurosyphilis has to be seriously considered in many unclear neurological cases. Atypical, often monosymptomatic clinical pictures make the diagnosis difficult. The exact analysis of the spinal fluid including antibodies against Treponema pallidum is necessary for the diagnosis. In contrast to former treatment schedules, now ultra high doses of penicillin are recommended and seem to be absolutely neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…So we found no evidence for an altered clinical pattern in the various neu rosyphilitic syndromes as stated in literature [1][2][3][4][5][6]. The 100% positive score in the newer specific treponemal tests (TPHA and FTAabs) in blood and CSF in both symptomatic and asymptomatic neurosyphilitic patients in the recent group is conform literature, as recently reviewed by Stöckli [4]. The 48% positive non-treponemal tests in CSF in symptomatic patients over the period 1970-1984 conform also more or less to the litera ture.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…So we found no evidence for an altered clinical pattern in the various neu rosyphilitic syndromes as stated in literature [1][2][3][4][5][6]. The 100% positive score in the newer specific treponemal tests (TPHA and FTAabs) in blood and CSF in both symptomatic and asymptomatic neurosyphilitic patients in the recent group is conform literature, as recently reviewed by Stöckli [4]. The 48% positive non-treponemal tests in CSF in symptomatic patients over the period 1970-1984 conform also more or less to the litera ture.…”
Section: Discussioncontrasting
confidence: 52%
“…The 48% positive non-treponemal tests in CSF in symptomatic patients over the period 1970-1984 conform also more or less to the litera ture. [4], However, the 0% positivity of these tests in the asymptomatic patients is low, when compared with the figures compiled by Stöckli. We have to keep in mind, however, that with the refined newer specific antitreponemal immunologic reactions such an tibody formation can be found much easier, e.g., with the TPHA index [7].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…First, only tetracycline and erythromycin are currently recommended by the Centers for Disease Control (6) and the World Health Organization (43) as alternate therapies for penicillin-sensitive individuals; there is evidence of treatment failure (14,23,39) and resistance (40) with erythromycin, and tetracycline is contraindicated for pregnant women and children (6,43). Second, the use of benzathine penicillin for the treatment of neurosyphilis has been questioned due to its poor bloodbrain barrier penetrability (21,41), leading physicians to substitute multiple injections or intravenous administration of aqueous penicillin G (6,41), procaine penicillin (6), or ceftriaxone (24) to ensure adequate treatment of these patients. Third, isolation of an erythromycin-resistant strain of T. pallidum from a syphilis patient (40) and evidence for a plasmid in T. pallidum (32) indicate that future development of widespread antibiotic resistance in this organism is possible.…”
mentioning
confidence: 99%
“…investigations have shown that neither of these regimens, even if administered in double doses or in combination with oral probenecid, results in therapeutic concentrations of penicillin in the cerebrospinal fluid (CSF) [2][3][4]. Thus treatment failure can be expected to occur in patients with syphilic infection of the central nervous system.…”
mentioning
confidence: 99%